RETRACTED: Lycorine Displays Potent Antitumor Efficacy in Colon Carcinoma by Targeting STAT3 - Wu, Song; Qiu, Yuling; Shao, Yingying; Yin, Shuangshuang; Wang, Rui; Pang, Xu; Ma, Junhong; Zhang, Chunze; Wu, Bo; Koo, Sangho; Han, Lifeng; Zhang, Yi; et al. (Frontiers in Pharmacology, 2018)
Signal transducer and activator of transcription 3 (STAT3) is an attractive therapeutic target for cancer treatment. In this study, we identify lycorine is an effective inhibitor of STAT3, leading to repression of multiple oncogenic processes in colon carcinoma. Lycorine selectively inactivates phospho-Stat3 (Tyr-705), and subsequent molecular docking uncovers that lycorine directly binds to the SH2 domain of STAT3. Consequently, we find that lycorine exhibits anti-proliferative activity and induces cell apoptosis on human colorectal cancer (CRC) in vitro. Lycorine induces the activation of the caspase-dependent mitochondrial apoptotic pathway, as indicated by activation of caspase and increase of the ratio of Bax/Bcl-2 and mitochondrial depolarization. Overexpressing STAT3 greatly blocks these effects by lycorine in CRC cells. Finally, lycorine exhibits a potential therapeutic effect in xenograft colorectal tumors by targeting STAT3 without observed toxicity. Taken together, the present study indicates that lycorine acts as a promising inhibitor of Stat3, which blocks tumorigenesis in colon carcinoma.